Use of total intravenous anaesthesia in Colombia: A national survey among active anaesthetists in Colombia☆. Issue 2 (April 2017) - Echeverry‐Marín, Piedad Cecilia; Arévalo, Jimmy; Pinzón, Paola; Vanegas‐Saavedra, Alberto; Leguizamón, Miryam
ABSTRACT : Introduction: : The use of total intravenous anaesthesia (TIVA) has been growing worldwide over the past 20 years due to the creation of new drugs and the development of new targetcontrolled infusion pumps, many of which have already been approved in the United States by the FDA (Food and Drugs Administration), in Europe and in Colombia. However, the use of TIVA has not been expanded yet as part of routine practice. Objective: : To determine the frequency of TIVA use in our country and to identify existing barriers for its implementation. Materials and methods: : Survey designed to determine the use of TIVA in general anaesthesia practice in Colombia. A representative random sample of the universe of anaesthetists registered in the database of the Colombian Society of Anaesthesiology and Resuscitation (S.C.A.R.E.) was calculated. Reminders were sent by e‐mail and some of the selected respondents were contacted by phone. Results: : Overall, 141 (32.4%) responses were obtained. The frequency of TIVA use was reported as Always, 7 (5.0%), Almost Always, 52 (36.9%), Hardly Ever, 57 (40.4%) and Never, 25 (17.7%). The techology used for TIVA administration included macro drip devices ( n = 30, 21.3%), volumetric pumps ( n = 76, 53.9%), TCI pumps ( n = 45, 31.9%), and computer programmes ( n = 9, 6.4%). The limitations identified for the use of TIVA included low availability of anaesthesia depth monitoring ( n = 68, 48.2%) and infusion pumps ( n = 52, 36.9%), lack of experience ( n = 41, 29.1%), little availability of workshops ( n = 26, 18.4%), low availability of medications ( n = 23, 16.3%), fear of intra‐operative recall ( n = 22, 15.6%), limited knowledge of pharmacology ( n = 18, 12.8%), increased anaesthesia time ( n = 13, 9.2%), and perceived difficulty for performing the technique ( n = 13, 9.2%). Conclusions: : The use of TIVA has been limited by the low availability of technology, lack of experience or knowledge among anaesthetists, and a preference for the balanced anaesthesia technique. Many anaesthesiologists prefer balanced techniques for general anaesthesia. Some devices used for TIVA administration raise concerns about patient safety. Uso de la Anestesia Total Intravenosa en Colombia: encuesta nacional dirigida a anestesiólogos activos en Colombia: RESUMEN: Introducción: : En los últimos 20 años el uso de la anestesia total endovenosa (TIVA) se ha expandido en todo el mundo debido a la creación de nuevos medicamentos y al desarrollo de nuevas bombas de infusión controladas por objetivo, muchas de las cuales ya han sido aprobadas por la Food and Drug Administration en USA, Europa y Colombia; sin embargo, el uso de TIVA aún no se ha expandiendo en la práctica rutinaria de la anestesia. Objetivo: : Investigar la frecuencia del uso de TIVA en nuestro país y las limitaciones que actualmente existen. Materiales y métodos: : Se diseño una encuesta para determinar el uso de la TIVA en Colombia. Se calculó una muestra aleatoria representativa de los anestesiólogos registrados en la Sociedad Colombiana de Anestesiología. Se enviaron recordatorios por correo electrónico y algunos anestesiólogos seleccionados se contactaron por vía telefónica. Resultados: : Se obtuvieron 141 (32, 4%) respuestas. La frecuencia del uso de TIVA fue reportada así: Siempre 7 (5, 0%), casi siempre 52 (36, 9%), casi siempre 57 (40, 4%) y nunca 25(17, 7%). La tecnología implementada para la administración de TIVA incluyó equipos de macro goteo ( n = 30: 21, 3%), bombas volumétricas ( n = 76; 53, 9%), bombas de TCI ( n = 45; 31, 9%) y programas de computador ( n = 9; 6, 4%). Las principales limitaciones para el uso de TIVA fueron la poca monitorización de la profundidad anestésica ( n = 68; 48, 2%) y de bombas de infusión ( n = 52; 36, 9%), falta de experiencia ( n = 41; 29, 1%), poca disponibilidad de talleres ( n = 26; 18, 4%), poca disponibilidad de medicamentos ( n = 23; 16.3%), temor al recordar intraoperatorio ( n = 22; 15, 6%), conocimiento limitado sobre farmacología ( n = 18; 12.8%), incremento en el tiempo de anestesia ( n = 13; 9, 2%), y la dificultad percibida de desarrollar la técnica ( n = 13; 9, 2%). Conclusiones: : El uso de TIVA se ha limitado por la poca disponibilidad de tecnología, falta de experiencia, y por que se prefiere la técnica balanceada para la anestesia. Algunos dispositivos usados para la administración de TIVA pueden comprometer la seguridad del paciente.